Analisis Pemecahan Masalah Teorema Pythagoras Ditinjau dari Gaya Belajar Sensing dan Intuition - Safitri, Evilia Eka; Ekawati, Rooselyna (Universitas Negeri Surabaya, 2025)
The Pythagorean Theorem is a basic mathematical concept that is widely applied in various fields, but students often have difficulty understanding and applying it effectively. Understanding students' learning styles, particularly sensing and intuition, can provide valuable insight into their problem-solving approaches and improve teaching strategies. This study aims to describe solving the Pythagorean theorem problem for students with sensing and intuition learning styles. This research uses a qualitative approach involving two class VIII junior high school students in Sidoarjo, each of whom consists of students with sensing and intuition learning styles. Data collection techniques were carried out by administering sensing and intuition learning style questionnaires, mathematical ability tests, problem solving tests, and interviews. The data analysis technique in this research uses learning style questionnaire scoring guidelines, mathematical ability test scoring guidelines, problem solving stage indicators according to Mason et al (2010) which consist of entry, attack and review stages, and data reduction from interviews to explore students' problem solving. The results showed that at the entry stage, students with a sensing learning style focused more on the concrete facts given in the problem, while intuition students tended to see patterns and conceptual relationships. At the attack stage, although both learning styles were able to solve the problem according to initial assumptions, there were similar errors in detailed calculations, especially those involving the concept of special triangle comparisons and root forms. At the review stage, sensing students focused more on checking the answer without looking for alternative solutions, while intuition students tried to explore other possible solutions even though they did not produce valid answers.